A GEMBA KAIZEN MODEL BASED ON BPMN FOR SMALL- AND MEDIUM-SCALE CONSTRUCTION BUSINESSES IN NIGERIA - Temitope Omotayo; Udayangani Kulatunga (Journal of Construction Project Management and Innovation)
This article presents a demonstration of how gemba kaizen, which is continuous improvement in the workplace, can be implemented using business process modelling and notation (BPMN). The scope of the study is construction businesses in Nigeria. In developing the BPMN model for construction businesses in Nigeria, the modus operandi regarding decision making and managing challenges which may be transferred to the cost planning was identified. The mixed-method approach was used to develop this model from the qualitative and quantitative findings. The survey strategy was employed for the analysis, covering eleven interviews and one hundred and thirty-five questionnaires from contractorsand cost and project managers in small- and medium-scale companies in Lagos, Nigeria. NVIVO 10 and descriptive statistics were used to assess the results. The findings of the study focused on the perception towards change, post-project reviews, openness to new ideas, and innovation. The study observed post-project reviews as the only significant indicator of continuous improvement in Nigerian small- and medium-scale construction companies. This result is not enough to indicate that there is continuous improvement. Therefore, the model design focused on continuous improvement activities for the companies. The creation of a BPM model elucidated the continuous improvement functions, stages and processes. This study may be implemented in construction companies in developing economies for improving the competitive advantage of small- and medium-scale construction companies.